2021
DOI: 10.1590/fst.35120
|View full text |Cite
|
Sign up to set email alerts
|

Seasonal variations in some quality parameters of milk produced in Khorasan Razavi Province, Iran

Abstract: In this trial, 60 samples of raw cow's milk collected during summer and winter in five collective centers from Khorasan Razavi Province of Iran were analyzed for penicillin residues, somatic cell counts (SCC), mesophilic counts (TMC) and adulteration materials. The mean penicillin level (0.57 ± 0.20 μg/L) was much lower than the maximum permitted level (MPL) recommended by the Codex Alimentarius Commission (4 μg/L). However, the mean SCC and TMC (Log 5.71 ± 0.08 cells/mL and Log 6.18 ± 0.11 colony forming unit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
1
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 19 publications
0
1
0
Order By: Relevance
“…A higher APC level during the dry season in raw milk has been reported by Elmoslemany et al (2010) (Canada), who found that the APC levels in summer were 0.33 and 0.21 times higher than in fall and winter, respectively [53]. Hajmohamnadi et al (2021) found the total bacteria count during summer (6.25 log cfu/mL) significantly higher than in winter (6.10 log cfu/mL) in raw milk collected from different parts of Iran [54]. In another similar study from Italy by Bertocchi et al (2014), they revealed that the APC load in raw milk collected during summer (9.99 log cfu/mL) and spring (9.87 log cfu/mL) was higher than in fall (9.84 log cfu/mL) and winter (9.83 log cfu/mL) [55].…”
Section: Total Bacterial Count (Apc) In Raw Milk Pasteurized Milk And...mentioning
confidence: 69%
See 1 more Smart Citation
“…A higher APC level during the dry season in raw milk has been reported by Elmoslemany et al (2010) (Canada), who found that the APC levels in summer were 0.33 and 0.21 times higher than in fall and winter, respectively [53]. Hajmohamnadi et al (2021) found the total bacteria count during summer (6.25 log cfu/mL) significantly higher than in winter (6.10 log cfu/mL) in raw milk collected from different parts of Iran [54]. In another similar study from Italy by Bertocchi et al (2014), they revealed that the APC load in raw milk collected during summer (9.99 log cfu/mL) and spring (9.87 log cfu/mL) was higher than in fall (9.84 log cfu/mL) and winter (9.83 log cfu/mL) [55].…”
Section: Total Bacterial Count (Apc) In Raw Milk Pasteurized Milk And...mentioning
confidence: 69%
“…In another similar study from Italy by Bertocchi et al (2014), they revealed that the APC load in raw milk collected during summer (9.99 log cfu/mL) and spring (9.87 log cfu/mL) was higher than in fall (9.84 log cfu/mL) and winter (9.83 log cfu/mL) [55]. In warm and humid environments, the growth and number of environmental bacteria in cows' bedding material increase owing to favorable temperature and humidity [54]. The bacteria most probably enter into dairy products in dairy farms that utilize traditional practices in countries like Ethiopia [56].…”
Section: Total Bacterial Count (Apc) In Raw Milk Pasteurized Milk And...mentioning
confidence: 99%
“…Similarly, Toghdory et al reported that as the environmental temperature increased, the level of milk protein and fat and the number of somatic cells decreased significantly [27]. Researchers in different studies have shown an increase in somatic cell count during the summer months [28,29]. It is estimated that this is due to the increased incidence of mastitis with temperature [29].…”
Section: Resultsmentioning
confidence: 95%
“…No recent publications using CP in the sector were identified in the literature. Therefore, the motivation for this study arises once the dairy industry has significant economic and social relevance in Brazil, with high production and market share (Hajmohammadi et al, 2020;Lopes et al, 2020;Messias et al, 2022).…”
Section: Introductionmentioning
confidence: 99%